Profesionalisme Guru dalam Perspektif Islam: Profesionalisme Guru dalam Perspektif Islam - Purwaningsih, Rahma Fitria; Muliyandari, Atika (Ngaji: Jurnal Pendidikan Islam, 2021)
Education in Indonesia still has a propensity to fully and deeply theoretical comprehensive cognitive aspects compared to students' skill and learning experience. As the facilitator in learning, teachers have to teach and be able to be a figure and a role model for either students or communities. In this case, the study aims to describe teachers' professionalism from the Islamic perspective. Teachers' problem in the teaching process is in the organizational learning system, which tends to be static and not really flexible. Meanwhile, a revolution of information technology presses the teacher to be dynamic for bringing on the civilized generation without losing the moral value. Professional teachers' identity to the students has Islamic values which are conformable with the competitions that should be own; thus, teachers should be prepared in adapting to the needs of the millennial era and connected with the Islamic teaching, like Ulul Albab, Al-Ulamaa', Al Muzakki, Ahl Ad-Dzikr, and Ar-Raskhun fi 'Ilm.